The Role of Moral Norms and Religious Orientation in Predicting Consumer’s Pro-Environmental Behavior - Hidayatullah, Havidz Kus; Ekasari, Ayu (Indonesian Journal of Sustainability Accounting and Management, 2023)
Sustainability has been popular in the recent marketing literature. Scholars take their role by investigating how to positively influence people to be more proactive in green consumption behavior. While a green attitude failed to predict green behavior, thus relying on a green attitude is not the solution. Scholars need to find out what factors need to be improved to shape consumers’ green attitudes. This study uses a relatively new perspective by examining the role of Moral Norms and Religious Orientation in predicting pro-green Behavior through forming Green Attitude Purchasing. Moral Norms and Religious Orientation, two common values which are highly concerned by most common societies in Indonesia, have never been tested together as predictors of green behavior. The proposed model is tested through hypothesis testing and 250 respondents who are daily convenience users of green products were involved. The sequential equation modeling analysis result shows that the model is fit, and all hypotheses are supported. Hence, Moral Norms and Religious Orientation can be used together to predict Green Behavior through forming of Green Purchasing Attitude. This finding contributes new perspectives that Moral and Religiosity can be applied simultaneously to any green marketing campaign, especially in Indonesia.